The influence of distributed leadership on the improvement of entrepreneurial subjects in secondary schools in Capricorn district, South Africa - Khutso Mankgele (Cita Konsultindo Research Center, 2023)
Entrepreneurial subjects are being phased out in some Limpopo schools in South Africa because of poor performance of learners in such subjects. This study examined the relationship between distributed leadership and curriculum implementation in secondary schools. The study used the quantitative research method, and the cross-sectional survey method was used to collect data from 115 respondents. Descriptive statistics, Pearson correlation, and regression analysis were used for data analysis. The results indicated significant positive relationships between distributed leadership and curriculum implementation in secondary schools Recommendations to improve distributed leadership in secondary schools include developing strategies that allow all teachers who are capable and willing to get an opportunity to lead certain areas of the school even if it is for shorter periods of time. Furthermore, there is a need to review and revisit the teacher’s provisioning model and ensure that entrepreneurial subjects are taught by a person who specialized in such a subject.